BrainBashers Puzzles

A Proof That 2 = 1:

1.           X = Y              let x=y
2.         X*X = XY             multiply by x on both sides
3.   X*X - Y*Y = XY - Y*Y       subtract y*y from both sides
4.  (X+Y)(X-Y) = Y(X-Y)         factorise
5.       (X+Y) = Y              divide by (x-y) on both sides
6.         Y+Y = Y              replace x with y
7.          2Y = Y              factorise
8.           2 = 1              divide by y on both sides

Where lies the flaw in the logic?

[Ref: ZIHG]


Printed from BrainBashers [www.brainbashers.com]